Evaluating Psychometric Characteristics of Detection Protocol of Malingering Stuttering - Arsia Thaghva; Majid Saleh; Vahid Donyavi; Bijan Shafei; Meisam Shafei; Ahmad Pourmohamad (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Stuttering is a disorder in fluency that is identified through involuntary interruptions in continuous speech. There are different types of the disorder, including growth stuttering with acquired and malingering origins. With respect to the law of exemption of stuttering individuals from military service, the issue of malingering is quite common. Since there is no standard tool to be used for deciding exemption, experts rely mostly on their personal knowledge and judgment, and because the measurements and perceptual judgments are made informally, it increases the likelihood of errors. Therefore, the preparation of a protocol to detect conscripts who are afflicted with malingered stuttering from those who suffer from real stuttering was the aim of the study, thereby, determining the conditions of exemption from military service. Materials & Methods This study is of validation type. Accessible simple non-probability sampling was used. First, different sections of the detection protocol of malingering stuttering was prepared, which consisted of structured interview, questionnaire for malingering stuttering, MMPI test, facilitator techniques, SSI4 test, and analysis of reading and speech sample. Then, sampling was done on 20 exemption applicants who were suspected to be malingering and, at the same time, on 15 applicants who had visited a clinic for a real stutter. Then, the features of the protocol were investigated, and the profile of malingering was prepared based on the results obtained from the detection protocol of malingered stuttering. Finally, the data were analyzed using different statistical methods and SPSS. Results Detection protocol of malingered stuttering was codified. With regard to Cronbach's alpha coefficient, which was equal to 0.76, for the detection questionnaire of malingered stuttering, the questionnaire was of good internal consistency. To determine the concurrent validity of the protocol (the results of the implementation of the protocol following the opinion of psychiatrists), Chi-square test was carried out, and no significant difference was found between the protocol and the comments of the psychiatrists (P>0.05). The protocol was of good construct validity. Finally, a profile was prepared to determine the status of conscription with respect to stuttering disorder based on the results for each participant. Conclusion According to the results, the detection protocol of malingering stuttering is of good internal consistency and concurrent validity. However, considering that the sample population was not large in the present study, it can be said that this study is a preliminary evaluation to find the psychometric features of the instruments, with the aim of laying the groundwork for further studies.